What Is the Evidence on Natural Recovery Over the Year Following Sports-Related and Non-sports-Related Mild Traumatic Brain Injury: A Scoping Review - Brady, Morgan; Hume, Patria A.; Mahon, Susan; Theadom, Alice (Frontiers in Neurology, 2022)
Background. Treatment approaches often differ dependent upon whether a person experiences a sports-related or a non-sports related brain injury, yet neurophysiological trauma to the brain is likely similar across injury mechanisms. Objective. To review current research and identify knowledge gaps on symptom presentation, recovery timeframes and outcomes between sport and non-sports related mTBI and how they are measured. Methods. A systematic search of key electronic databases including PubMed, SPORTDiscus, Embase, MEDLINE, and CINAHL was conducted until 10th March 2021. Articles were included if they were available in English; full text published in a peer reviewed journal; had prospective or retrospective study designs; reported data on mild TBI cases >16 years of age and included at least one follow-up assessment. The search strategy elicited 12,212 abstracts which were compared against the inclusion criteria. A standardised data extraction tool was used to determine the participant characteristics, assessment methods and recovery timeframes explored. Results. A total of 42 (18 sport; 24 non-sport) articles were identified. All identified sports articles were conducted in the USA (N=15) or Canada (N=3). Non-sports related injury articles were conducted across the USA (N=6) Canada N=3), Australasia (N= 3) Europe (N=9), Taiwan (N=2) and Morocco (N=1). There were notable methodological differences between those looking at SR-TBI and those exploring non-sports related mTBI, including definitions, type of outcome measures and timing of follow up assessment. Diversity in outcome measures prevented direct comparison of clinical presentation or recovery trajectories between sport and non-sport related injuries. Only one article reported on both sports related and non-related TBI separately within the same study. This study revealed no differences in recovery timeframes or overall symptom burden. Discussion. Whilst there is clear benefit in researching specific subpopulations in detail, standardised outcome measures and follow up timeframes are needed across the full mTBI spectrum to facilitate understanding of similarities and differences between these injury types. This review identified a lack of studies with equivalent methodological features to enable comparisons in order to optimise and tailor clinical treatment accordingly.